THE MAIN DIDACTIC PRINCIPLES OF TEACHING INFORMATICS : Ж.Ж. Aтaмурадов - Atamuradov, Jamshid (Центр Научных Публикаций (buxdu.uz), 2021)
This article discusses the didactic principles used in the teaching of computer science. Keywords: principles, research, clarification, form of thinking, science, clarity.